PROGRAM LATIHAN FIFA 11 PLUS TERHADAP PENINGKATAN KONDISI FISIK SISWA EKSTRAKURIKULER SMA NW NARMADA - Yusuf, Putra Muhammad; Suprawesta, Lalu; Zainuddin, Fadli (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2019)
Physical condition is an important part in sports in the form of intact components that cannot be separated both in terms of improvement and maintenance. The component is a basic biometric consisting of strength, endurance, speed, coordination, and flexibility. The FIFA 11 Exercise Program plus is a training training facility designed by the FAFA Medical Assessment and Research Center (F-MARC) in collaboration with other Sports institute companies namely the Sport Trauma Research Center of Oslo and the Santa Monica Orthopedic and Sports Medicine Research Foundation. The method used in this study was an experiment with one group pretest-posttest design. The type of research used in this study is qualitative. The population in this study was the estrangular students of NW Narmada High School totaling 15 people. The sample technique used in this study was purposive sampling. Data collection techniques in this study were documentation, observation and experiment techniques. Research instruments used a balance test using Balance One tools, agility tests using shuttle run, test the power of the muscles pushing using the Back And Leg Dynamometer. Data analysis techniques with rumust-test for sample type and processing using the SPSS version 17 program with a significant level of 5% (Î± = 0.05). The pre and post physical condition mean values obtained p = 0.003 on balance, p = 0.000 on agility and strength. This shows a significant difference, with a significant difference in the value of p <0.05. The output in this study is a non-accredited national journal scientific publication.